Effect of pelvic floor muscle exercise programme on stress urinary incontinence among pregnant women - Bussara Sangsawang (2018)
Aim. This article is a report of a study of the effects of a pelvic floor muscle exercise programme on the severity of stress urinary incontinence in pregnant women. Background. Pregnancy is main risk factor for the development of stress urinary incontinence. Stress urinary incontinence can be cured by pelvic floor muscle exercise which is a safe inexpensive treatment with no complications and does not require the use of instruments. Methodology. A quasi-experimental study, pre-post test with control group design was used at the antenatal care unit in a tertiary care hospital between June and October of 2006. The participants were 66 pregnant women who had stress urinary incontinence with gestational ages of 20-30weeks. The main outcome measure was severity of stress urinary incontinence which comprised frequency and amount of urine leakage and perceived severity of stress urinary incontinence. Results. After the experimental group's participation in the pelvic floor muscle exercise programme, the frequency and amount of urine leakage and the score of perceived stress urinary incontinence severity were significantly lower than the same scores before participation in the programme. In addition, women in the experimental group had frequency and volume of urine leakage, and score of perceived stress urinary incontinence severity after participation significantly lower than those in the control group. Conclusion. The 6-week pelvic floor muscle exercise programme was able to decrease the severity of symptoms in pregnant women with stress urinary incontinence. © 2011 Blackwell Publishing Ltd.